On Philosophical and Aesthetical Problems in L Pirandelo’s Dramas - Baužytė, Galina (Problemos, 1973)
Luigi Pirandello, Italian playwright, novelist and short-story writer, touched upon important philosophical and psychological problems, which had been also reflected in the relativist, agnostical, Freudian and existentialist theories. He developed an original conception of personality, emphasizing the role of the sphere of consciousness and subconsciousnes. In his early dramas (Right You Are, 1918; Life, Which I Give You, 1924) L. Pirandello maintained the relativist theory of the impossibility to know objective truth, i.e., the predominance of man’s subjective images of life. Thus the main conflict of L. Pirandello’s dramas arose – the conflict between illusion and reality. This conflict is especially pronounced in Enrico IV, one of his best dramas. In Six Personages in Search of the Author and Tonight We Improvise the author solved the problem of the relationship between art and life, affirming the autonomy of artistic reality.